Commitment to Academic Exchanges in the Age of COVID-19: A Case Study of Arrival and Quarantine Experiences from the Republic of Korea - Stewart, William; Kim, Bo Myung (Journal of International Students, 2021)
The suspension of international student mobility programs has been common due to COVID-19. In the Republic of Korea, the successful management of the pandemic allowed borders to remain open and mobility to continue. In Spring 2020, however, the Korean government started requiring quarantine-upon-arrival for all inbound travel; the sudden announcement created confusion. The Fall semester would see students arrive with no knowledge of how quarantines would work or in what ways the isolation period might affect them. Student motivations for exchanges during a global pandemic with increased health risks, mobility obstacles, and stresses were unknown. This case study reports the arrival/quarantine experiences of 10 exchange students in Seoul, Korea. Students’ views and expectations of Korea as a safe study destination were juxtaposed with tumultuous arrival experiences. We discuss these findings in terms of the academic exchange life cycle and the importance of resource/service accessibility amid novel pandemic-based norms.